Strategi Pengembangan Pariwisata Berbasis Budaya pada Objek Wisata Tamborasi di Desa Tamborasi Kecamatan Iwoimendaa Kabupaten Kolaka - Aminadap Aminadap; Nasruddin Suyuti (JURNAL KABANTI: Kerabat Antropologi, 2023)
This study aimed to determine the role of the government and the community of Tamborasi village in the development of culture-based tourism at Tamborasi Tourism Object in Tamborasi Village, Iwoimendaa Subdistrict, Kolaka Regency. The informants in this study were 13 people who had long lived in the vicinity of the Tamborasi tourism object as well as the Kolaka Regency government apparatus in Tamborasi village. This research is a descriptive study that uses a qualitative approach so that data collection uses observation, interviews, and documentation. The data analysis was performed using a qualitative descriptive method with an ethnographic approach. The results showed that (1) the role of the local government and the people of Tamborasi Village in developing culture-based tourism at Tamborasi Tourism Object in Tamborasi Village, Iwoimendaa District, Kolaka Regency, namely by utilizing the resources and opportunities they have, providing education about tourism to the community, increasing cooperation with the government, increase promotion, establish the village regulations for sterilization of tourist areas, improve the quality of human resources, increase supervision in the management of tourist objects, management and arrangement of facilities and infrastructure, cooperate with the government and private sector, and maintain the existing culture of the community. (2) Supporting factors in the development of Tamborasi Tourism Object, namely natural potential, good security conditions, the atmosphere of the tourist attraction that provides comfort, and good road conditions. While the inhibiting factors are the long distance from the city of Kendari, the lack of promotion of tourism objects, the simple development program for tourism objects, the limited budget for the cost of facilities and infrastructure for tourist objects, and the lack of a professional workforce in managing tourist objects.